A comparative evaluation of Transurethral Electro-Vaporisation of Prostate (TUEVP) versus Transurethral Resection of Prostate (TURP) for Benign Prostatic Hyperplasia (BPH) - Saini, Rijul; Saxena, Kartik; Makkar, Gourav S.; Shivam, Shekhar; Desai, Sandip; Singh, Shivam; Gupta, Nishi (International Surgery Journal, 2017)
Background: Transurethral Resection of Prostate (TURP) has been gold standard of surgical treatment of BPH but nonetheless it is associated with many complications. Transurethral Electro-Vaporisation of Prostate (TUEVP) is a new promising modality which has similar results and better side effect profile. Methods: A prospective, randomised, comparative study was conducted on seventy patients with symptomatic BPH in the Surgery department of Sanjay Gandhi Memorial Hospital, Delhi over two years starting from December 2014. These patients were randomly assigned to two groups- A and B using online random number generator. Patients of group A underwent TUEVP and those of group B underwent TURP. Overall patient satisfaction, patient safety, procedural efficacy and operative ease of the surgeon were compared. Results: Mean operative time (42.1 min in TUEVP and 38.4 min in TURP) and complication rates (14.3% in TUEVP and 11.4% in TURP) were comparable in both groups. Intra-operative bleeding was significantly less (2.9% in TUEVP; 22.9% in TURP) and visual clarity of operative field was significantly better in TUEVP (persistently clear in 97.1% in TUEVP; 77.1% in TURP). The mean catheterisation time (1.14 days in TUEVP and 2.51 days in TURP) and hospitalisation time (2.14 days in TUEVP and 3.1 days in TURP) were significantly shorter in TUEVP. Conclusions: TUEVP is comparable to TURP in terms of patient satisfaction, safety, operative time and procedural efficacy. TUEVP has shorter duration of catheterisation and hospitalisation and is better than TURP in terms of intra-operative bleeding and operative ease of the surgeon.